MASALAH DAN PERANAN CO2 PADA PRODUKSI TANAMAN - Sutoyo Sutoyo (Universitas Tribhuwana Tunggadewi, 2011)
Carbon dioxide is a gas that can be as the greenhouse effect. The greenhouse effect can occur naturally, and can occur due to human activities. The process of the greenhouse effect associated with the recycling flow of solar energy. Increased levels of CO2 in the atmosphere due to human activity, especially transportation and industrial activities so that increasing consumption of fossil fuels, and changes in land use. These activities are difficult to control because of the demands for the fulfillment of a better life. On the other hand mitigation and adaptation efforts to reduce the CO2 impact has not been completely worked well. On evaporation and temperature changes due to the greenhouse effect of CO2 and global warming impacts of drought, rising sea water, and other sector losses, but profitable irrigated agricultural land, such as plant seeds and nuts. The direct effect of increased CO2, positive impact on crop production through increased leaf and canopy photosynthesis, its effect on C4 plants also increase water use efficiency because it reduces the opening of stomata